Characteristics that make trophy hunting of giant pandas inconceivable. Issue 4 (15th April 2020) - Montgomery, Robert A.; Carr, Madeline; Booher, Charlie R.; Pointer, Abigail M.; Mitchell, Brendan M.; Smith, Natalie; Calnan, Keegan; Montgomery, Georgina M.; Ogada, Mordecai; Kramer, Daniel B.
Abstract: In November 1928, Theodore Jr. and Kermit Roosevelt led an expedition to China with the expressed purpose of being the first Westerners to kill the giant panda (Ailuropoda melanoleuca). The expedition lasted 8 months and resulted in the brothers shooting a giant panda in the mountains of Sichuan Province. Given the concurrent attention in the popular press describing this celebrated expedition, the giant panda was poised to be trophy hunted much like other large mammals around the world. Today, however, the killing of giant pandas, even for the generation of conservation revenue, is unthinkable for reasons related to the species itself and the context, in time and space, in which the species was popularized in the West. We found that the giant panda's status as a conservation symbol, exceptional charisma and gentle disposition, rarity, value as a nonconsumptive ecotourism attraction, and endemism are integral to the explanation of why the species is not trophy hunted. We compared these intrinsic and extrinsic characteristics with 20 of the most common trophy‐hunted mammals to determine whether the principles applying to giant pandas are generalizable to other species. Although certain characteristics of the 20 trophy‐hunted mammals aligned with the giant panda, many did not. Charisma, economic value, and endemism, in particular, were comparatively unique to the giant panda. Our analysis suggests that, at present, exceptional characteristics may be necessary for certain mammals to be excepted from trophy hunting. However, because discourse relating to the role of trophy hunting in supporting conservation outcomes is dynamic in both science and society, we suspect these valuations will also change in future. Abstract : Article impact statement : Giant panda's symbolism, gentle nature, endemism, rarity, and value as an ecotourism target make trophy hunting the species unthinkable. Características que Hacen que la Caza de Trofeos de Pandas sea Inconcebible Resumen: En noviembre de 1928, Theodore Jr. y Kermit Roosevelt lideraron una expedición a China con el propósito explícito de ser los primeros occidentales en cazar un panda gigante (Ailuropoda melanoleuca). La expedición duró ocho meses y terminó con los hermanos disparándole a un panda gigante en las montañas de la provincia de Sichuan. Dada la atención simultánea en la prensa popular que describía esta expedición celebrada, se posicionó al panda gigante como un nuevo objetivo de la caza de trofeos como muchos otros mamíferos alrededor del mundo. Sin embargo, hoy en día, la caza de pandas gigantes, incluso para la generación de ingresos para la conservación, es impensable debido a razones relacionadas con la misma especie y el contexto de tiempo y espacio en el que se popularizó a la especie en Occidente. Descubrimos que el estado del panda gigante como símbolo de conservación, su excepcional carisma y temperamento gentil, rareza, valor como atracción ecoturística no consuntiva y su endemismo son integrales para explicar por qué la especie no se caza como trofeo. Comparamos estas características intrínsecas y extrínsecas con 20 de los mamíferos más comunes en la caza deportiva para determinar si los principios que aplican para los pandas gigantes pueden generalizarse para otras especies. Mientras que ciertas características de los 20 mamíferos se alinearon con las del panda gigante, muchas no lo hicieron. El carisma, el valor económico y el endemismo, en particular, fueron comparativamente únicos para el panda gigante. Nuestro análisis sugiere que, actualmente, las características excepcionales pueden ser necesarias para que ciertos mamíferos no sean objeto de la caza deportiva. Sin embargo, ya que el discurso relacionado con el papel de la caza deportiva en el apoyo a los resultados de conservación es dinámico tanto en la ciencia como en la sociedad, sospechamos que estas valoraciones también cambiarán en el futuro. 摘要: 1928 年 11 月, 小西奥多·罗斯福和柯密特·罗斯福带领探险队到达中国, 他们的目的是成为第一批成功猎杀大熊猫 ( Ailuropoda melanoleuca) 的西方人。这次探险持续了 8 个月, 最终两兄弟在四川省山区射杀了一只大熊猫。考虑到公众媒体对这次著名探险的大量报道, 大熊猫很可能会像世界上其它大型哺乳动物那样成为战利品狩猎的对象。而今天, 由于大熊猫物种本身及其在西方国家得到宣传普及的时空范围, 即便是为了获得保护收益而捕杀大熊猫也让人难以想象。我们发现, 大熊猫作为物种保护象征的地位、非凡的魅力及温和的性情、稀有性、作为非消耗性生态旅游资源的价值以及地方特有性, 是解释这个物种为什么没有受到战利品狩猎的必要因素。我们将大熊猫这些内在和外在的特征与 20 种战利品狩猎中最常见的哺乳动物的特征进行了比较, 分析了适用于大熊猫的原则是否能推广到其它物种身上。结果表明, 虽然受到战利品狩猎的 20 种哺乳动物的某些特征与大熊猫一致, 但有许多并不相同。特别是魅力、经济价值和地方特有性这几个因素, 均为大熊猫相对独特的特征。我们的分析表明, 目前, 某些哺乳动物若要免受战利品狩猎, 可能需要具备特殊的特征。不过, 由于在科学和社会方面对于战利品狩猎在保护成效中的作用的讨论仍在不断进行, 我们认为以上评估在未来也可能发生改变。 【翻译: 胡怡思; 审校: 聂永刚】